NY-ESO-1 specific TCR engineered T-cells mediate sustained antigen-specific antitumor effects in myeloma - Rapoport, Aaron P. (Nat Med, 2015)
Despite recent therapeutic advances, multiple myeloma (MM) remains largely incurable. Herein we report results of a phase I/II trial to evaluate the safety and activity of autologous T-cells engineered to express an affinity-enhanced T-cell receptor (TCR) recognizing a naturally processed peptide shared by the cancer-testis antigens NY-ESO-1 and LAGE-1. Twenty patients with antigen-positive MM received an average 2.4×10(9) engineered T cells two days after autologous stem cell transplant (ASCT). Infusions were well-tolerated without clinically apparent cytokine release syndrome, despite high IL-6 levels. Engineered T-cells expanded, persisted, trafficked to marrow and exhibited a cytotoxic phenotype. Persistence of engineered T cells in blood was inversely associated with NY-ESO-1 levels in the marrow. Disease progression was associated with loss of T cell persistence or antigen escape, consistent with the expected mechanism of action of the transferred T cells. Encouraging clinical responses were observed in 16 of 20 patients (80%) with advanced disease, with a median progression free survival of 19.1 months. NY-ESO-1/LAGE-1 TCR-engineered T-cells were safe, trafficked to marrow and showed extended persistence that correlated with clinical activity against antigen-positive myeloma.